2021
DOI: 10.52429/selju.v4i1.568
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Flashcard In Teaching English Vocabularies By Young Mothers

Abstract: This study aims to determine how to apply flashcards in teaching English vocabulary by young mothers in the Dawis PKK Desa Dua Belasan RT I RW III Jombor Kec. Bendosari Kab Sukoharjo. The problems in this study were examined by qualitative descriptive research because the results of the approach were explained by using words. This research was conducted in the village of Dua belasan Jombor Sukoharjo. Meanwhile, data collection techniques are observation and documentation. The use of flashcards to teach English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Students who possess an extensive vocabulary are capable of demonstrating proficiency in all four language skills. On the other hand, inadequate vocabulary knowledge hinders their ability to excel in these areas (Frijuniarsi & Marlianingsih, 2016;Nurnaningsih, 2022). The interconnection between vocabulary and the four English skills is well-established, as noted by Hornby (1984, as cited in Zalmansyah, 2013) and Da Silva Wadu and Supeno (2021).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Students who possess an extensive vocabulary are capable of demonstrating proficiency in all four language skills. On the other hand, inadequate vocabulary knowledge hinders their ability to excel in these areas (Frijuniarsi & Marlianingsih, 2016;Nurnaningsih, 2022). The interconnection between vocabulary and the four English skills is well-established, as noted by Hornby (1984, as cited in Zalmansyah, 2013) and Da Silva Wadu and Supeno (2021).…”
Section: Introductionmentioning
confidence: 94%
“…Pavia et al (2019) suggest that English songs can stimulate students to acquire new vocabulary, and the repetition of songs aids in the retention of vocabulary. Nurnaningsih (2022) and Isnaini and Aminatun (2021) have also found that English songs can assist students in overcoming difficulties in vocabulary acquisition and expressing their ideas in English. Wardiman et al (2022) argue that incorporating English songs into the learning process promotes active and enjoyable learning, leading to improved vocabulary mastery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they used Google Classroom to create a class, give assignments, and do some written tasks in English. Meanwhile, YouTube was utilized to foster comprehension or insight regarding the supporting English materials containing some learning videos completed by elaborations (Nurnaningsih, 2021;Wahyuningsih & Dewi, 2019). The last application is Zoom Meeting which was used for virtual communication via video conference.…”
Section: The Implementation Stage Of E-learningmentioning
confidence: 99%
“…Communication within language use is conducted by people to express their wants, messages, information, and ideas (Adi & Fadilah, 2021). Words are an important aspect of a language which is dealt with in morphology, despite research on words and their use that can be done through, for example, words within flashcards for English vocabulary teaching (Nurnaningsih, 2021) and learning vocabulary through English songs and their perceived views (Faisal & Putri, 2023). The research on words is of morphological analysis, thus researching on words through the study of them, i.e.…”
Section: Introductionmentioning
confidence: 99%